2011
DOI: 10.1186/1472-6955-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment in outpatient care for patients with chronic kidney disease - from the family member's perspective

Abstract: BackgroundFamily members of persons with pre-dialysis chronic kidney disease may experience feelings of vulnerability and insecurity as the disease follows its course. Against this background, the aim of the present study was to explore empowerment in outpatient care as experienced by these family members.MethodsAn inductive approach for qualitative data analysis was chosen. The study sample comprised 12 family members of pre-dialysis patients at an outpatient kidney clinic. Two interviews with each family mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 41 publications
2
53
0
4
Order By: Relevance
“…The participants described knowledge acquisition as essential for their empowerment, a finding supported by previous researchers [18, 19]. They sought information from literature, the Internet, mass media programs, and peers, and by talking to healthcare providers.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The participants described knowledge acquisition as essential for their empowerment, a finding supported by previous researchers [18, 19]. They sought information from literature, the Internet, mass media programs, and peers, and by talking to healthcare providers.…”
Section: Discussionsupporting
confidence: 59%
“…They sought information from literature, the Internet, mass media programs, and peers, and by talking to healthcare providers. Patients have previously described seeking information outside healthcare encounters, so as to acquire an understanding of the disease [19]. Previous findings have underlined the need for healthcare providers to support patients by providing relevant knowledge that is important to them [10, 20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, findings from a study of patients receiving dietary advice for cardiac rehabilitation indicated that patients stopped following dietary recommendations after receiving contradictory advice from other health professionals . Further research into the relationship between trust in the health professional and patient empowerment is warranted …”
Section: Discussionmentioning
confidence: 99%
“…Dessa maneira, o conhecimento fornece responsabilidade e autonomia à pessoa para viver de maneira mais digna e humana; isto é, ajuda o usuário a tomar decisões e desenvolver habilidades para cuidar de si, emancipando-o (7) .…”
Section: Christiany Moçali Gonzalez Maria Luiza De Oliveira Teixeiraunclassified